Modeling and experimental investigation on ultrasonic-vibration-assisted grinding - Qin, Na (Kansas State University, 2011)
Poor machinability of hard-to-machine materials (such as advanced ceramics and titanium) limits their applications in industries. Ultrasonic-vibration-assisted grinding (UVAG), a hybrid machining process combining material-removal mechanisms of diamond grinding and ultrasonic machining, is one cost-effective machining method for these materials. Compared to ultrasonic machining, UVAG has much higher material removal rate while maintaining lower cutting pressure and torque, reduced edge chipping and surface damage, improved accuracy, and lower tool wear rate. However, physics-based models to predict cutting force in UVAG have not been reported to date. Furthermore, edge chipping is one of the technical challenges in UVAG of brittle materials. There is no report related to effects of cutting tool design on edge chipping in UVAG of brittle materials. The goal of this research is to provide new knowledge of machining these hard-to-machine materials with UVAG for further improvements in machining cost and surface quality. First, a thorough literature review is given to show what has been done in this field. Then, a physics-based predictive cutting force model and a mechanistic cutting force model are developed for UVAG of ductile and brittle materials, respectively. Effects of input variables (diamond grain number, diamond grain diameter, vibration amplitude, vibration frequency, spindle speed, and federate) on cutting force are studied based on the developed models. Interaction effects of input variables on cutting force are also studied. In addition, an FEA model is developed to study effects of cutting tool design and input variables on edge chipping. Furthermore, some trends predicted from the developed models are verified through experiments. The results in this dissertation could provide guidance for choosing reasonable process variables and designing diamond tools for UVAG.
Keywords: Ultrasonic-vibration-assisted grinding; Cutting force; Brittle materials; Ductile materials; Interaction effects; Edge chipping; Engineering (0537)